Efficacy of Multidomain Intervention Against Physio-cognitive Decline Syndrome: A Cluster-randomized Trial. (July 2021) - Liang, Chih-Kuang; Lee, Wei-Ju; Hwang, An-Chun; Lin, Chu-Sheng; Chou, Ming-Yueh; Peng, Li-Ning; Lin, Ming-Hsien; Chen, Liang-Kung
Highlights: PCDS features the mutual declines of physical and cognitive function of older people. 18.9% of the community-dwelling older persons had PCDS. Multidomain intervention improved cognitive performance of PCDS, as well as some subdomains of physical function PCDS is a potentially reversible condition that may prevent disability & dementia. Abstract: Backgrounds: To investigate the efficacy of a community group-based intervention among community-dwelling older adults with physio-cognitive decline syndrome (PCDS). Methods: A prospective cluster randomized controlled trial included 733 community-dwelling older adults with adjusted Montreal Cognitive Assessment (MoCA adj) scores >18 from 40 community-based sites across Taiwan. PCDS was defined as the concomitant presence of physical declines, i.e., slowness and/or weakness plus dysfunction in any cognitive domain. The multidomain intervention integrated physical exercise, cognitive training, nutritional advices and health education lessons. Conventional health education in control group entailed periodic telephone calls to offer participants health education and advice. The primary outcome was the mean differences of MoCA adj total scores and all domains of MoCA adj between baseline and 6- and 12-month follow-up in each group of PCDS, cognitive dysfunction, mobility-type frailty and normal functioning, and the secondary outcomes included the changes of frailty score, handgrip strength, gait speed and physical activity. Intervention effects were analysed using a generalized linear mixed model. Results: Overall, 18.9% of the study sample had PCDS. Multidomain intervention for 12 months significantly improved cognitive performance in people with PCDS, and those with cognitive dysfunction only. An early benefit on visuo-spatial executive function was seen in older adults with mobility-type frailty. Intervention also improved frailty scores among participants with mobility-type frailty, handgrip strength for participants with PCDS, and gait speed in the normal group. Conclusions: PCDS is a potentially reversible condition that may prevent subsequent disability and dementia, which deserves further investigation to confirm the long-term effects.